1976
DOI: 10.1111/j.1365-2125.1976.tb00606.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low doses of amylobarbitone sodium and diazepam on human performance.

Abstract: The effects of diazepam (2.5 and 5 mg) and amylobarbitone sodium (50 and 100 mg) on performance and subjective effects were assessed in a group of twelve healthy subjects under standardised conditions. Treatments were administered orally at weekly intervals according to a balanced design and under double‐blind conditions. The tests of performance most sensitive to drug effects in these healthy subjects were either prolonged and monotonous and gave the subject no feedback on performance, or required short term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
1

Year Published

1978
1978
1995
1995

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 17 publications
5
39
1
Order By: Relevance
“…It therefore appears that the lorazepam deficits in learning are closely related to self-ratings of the sedative action of the drug. Deficits in performance in learning tasks have been found to parallel ratings of sedation after administration of other CNS depressants (Hart et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…It therefore appears that the lorazepam deficits in learning are closely related to self-ratings of the sedative action of the drug. Deficits in performance in learning tasks have been found to parallel ratings of sedation after administration of other CNS depressants (Hart et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Hart et a/. 8 showed that the mental functions required for the test are particularly sensitive to benzodiazepines and, consequently, this test would be expcctcd to provide a good asscssmcnt of the effect of the drug. Certainly this test proved the most sensitive determinant of midazolam sedative activity in this study.…”
Section: Discussionmentioning
confidence: 99%
“…a few hours after ingestion of diazepam has been observed by Hart et al (1976) with a variety of tasks including auditory vigilance, reaction time, shortterm memory and digit symbol substitution. With temazepam our results were comparable with those of Hindmarch (1975), and so suggested a residual effect on performance with the 30 mg dose.…”
Section: Studies With Barbituratesmentioning
confidence: 99%